JADIDS SCHOOL IN TURKESTAN - Abdurahim Khasanovich Khasanov (European Science Publishing, 2024)
In this article explains about the enlighteners of Turkestan - the Jadids - the foundation for the movement to reform school education, turning the traditional educational centers of the ancient style that emerged in the Middle Ages into schools of a new method that provide modern knowledge. As a result, modern education and training, European civilization and the goal of serving its national culture, the modernist movement developed, schools of a new method were opened and began to educate young people.
Keywords: Jadids, shool, lesion, moral education, modern education and training, to reform school education, European civilization, schools of a new method, national culture.